Path-Breakers: How Does Women's Political Participation Respond to Electoral Success? - Sonia R. Bhalotra; Irma Clots-Figueras; Lakshmi Iyer (Institute for the Study of Labor (IZA), 2013)
This paper analyzes the effect of a woman's electoral victory on women's subsequent political participation. Using the regression discontinuity afforded by close elections between women and men in India's state elections, we find that a woman winning office leads to a large and significant increase in the share of female candidates from major political parties in the subsequent election. This stems mainly from an increased probability that previous women candidates contest again, an important margin in India where a substantial number of incumbents do not contest re-election. There is no significant entry of new female candidates, no change in female or male voter turnout and no spillover effects to neighboring areas. Further analysis points to a reduction in party bias against women candidates as the main mechanism driving the observed increase in women's candidacy.
Keywords: J16; J71; P16; 330; candidacy; gender; politics; India